2016
DOI: 10.1063/1.4953261
|View full text |Cite
|
Sign up to set email alerts
|

On-chip near-infrared spectroscopy of CO2 using high resolution plasmonic filter array

Abstract: We report an ultra-compact, cost-effective on-chip near-infrared spectroscopy system for CO2 sensing using narrow-band optical filter array based on plasmonic gratings with a waveguide layer. By varying the periodicity of the gratings, the transmission spectra of the filters can be continuously tuned to cover the 2.0 μm sensing window with high spectral resolution around 10 nm. Our experimental results show that the on-chip spectroscopy system can resolve the two symmetric vibrational bands of CO2 at 2.0 μm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The most important example is the color camera that relies three spectral filters: Red(R), Green(G), Blue(B). To go beyond three spectral bands, Fabry-Perot 13 and plasmonic filters 12,27,29 have been developed. However, these resonant filters have simple Lorentz line shapes and lack the spectral diversity to provide high spectral resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The most important example is the color camera that relies three spectral filters: Red(R), Green(G), Blue(B). To go beyond three spectral bands, Fabry-Perot 13 and plasmonic filters 12,27,29 have been developed. However, these resonant filters have simple Lorentz line shapes and lack the spectral diversity to provide high spectral resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Hole array periodicity is varied to tune the SP resonance wavelength causing spectral shifts in the corresponding spectral curves. Recently, plasmonic lters composed of periodic microhole arrays in noble metals like gold (Au), and silver (Ag) are demonstrated by exploiting SSP resonance [21][22][23]. Jang et al further demonstrated spectral imaging with a square array of micron-sized holes in Au lm on gallium arsenide dielectric as an SSP structure [24].…”
Section: Introductionmentioning
confidence: 99%
“…We note that our approach is not limited to this wavelength range, however. As our plasmonic filters are fabricated by lithography, evaporation, and lift-off, their operating wavelength can be readily shifted from the visible to the mid-IR [24,[37][38][39][40][41][42][43][44][45][46] by adjusting the geometric parameters and, if nec-essary, the substrate material. Unlike previous works on molecular and gas sensing using infrared metasurfaces, [47][48][49][50] the working principle of our device does not rely on the analyte molecules being in the near-field of the metasurfaces, e.g.…”
Section: Introductionmentioning
confidence: 99%